Effect of the Interaction Between Pre-pregnancy Body Mass Index and Fresh/Frozen Embryo Transfer on Perinatal Outcomes of Assisted Reproductive Technology-Conceived Singletons: A Retrospective Cohort Study - Qu, Pengfei; Mi, Yang; Zhao, Doudou; Wang, Min; Dang, Shaonong; Shi, Wenhao; Shi, Juanzi (Frontiers in Endocrinology, 2020)
Objective: To demonstrate the association between pre-pregnancy maternal overweight, obesity and perinatal outcomes of singletons conceived by assisted reproductive technology (ART). Design: Retrospective cohort study from 2006–2015 data from a single ART center. Setting: Assisted Reproduction Center, Northwest Women’s and Children’s Hospital, Xi’an, Northwestern China. Patients: We included 7,818 women undergoing ART and their singleton infants. Interventions: None. Main Outcome Measure: The primary outcome measures were preterm birth (PTB), macrosomia, low birth weight (LBW), small for gestational age (SGA) and large for gestational age (LGA). Results: We experienced an increase in the risk of PTB, macrosomia and LGA in overweight and obese groups compared to normal weight groups (PTB: overweight vs normal weight: OR = 1.44, 95% CI: 1.18–1.75; obesity vs normal weight: OR = 1.53, 95% CI: 1.04–2.25; macrosomia: overweight vs normal weight: OR = 1.78, 95% CI: 1.48–2.14; obesity vs normal weight: OR = 2.16, 95% CI: 1.52–3.06; LGA: overweight vs normal weight: OR = 1.63, 95% CI: 1.39–1.90; obesity vs normal weight: OR = 2.11, 95% CI: 1.57–2.83). We observed a significant interaction between maternal BMI and fresh/frozen embryo transfer on PTB and LGA (P = 0.030; P = 0.030). Fresh embryo transfer significantly increased the effect of maternal BMI on LGA (fresh: OR = 1.14, 95% CI: 1.10–1.18; frozen: OR = 1.09, 95% CI: 1.04–1.13), and frozen embryo transfer increased the effect of maternal BMI on PTB (fresh: OR = 1.03, 95% CI: 0.99–1.08; frozen: OR = 1.09, 95% CI: 1.04–1.15). Conclusions: Pre-pregnancy maternal overweight and obesity was associated with higher risks of PTB, macrosomia, and LGA in ART-conceived singletons. These associations were affected by the timing of embryo transfer (fresh/frozen embryo transfer). Therefore, we recommend women before ART to maintain a normal BMI for the prevention of adverse perinatal outcomes.